A taxonomy of generic clinical questions: classification study. Issue 7258 (12th August 2000) - Ely, John W; Osheroff, Jerome A; Gorman, Paul N; Ebell, Mark H; Chambliss, M Lee; Pifer, Eric A; Stavri, P Zoe
Abstract: Objective: To develop a taxonomy of doctors' questions about patient care that could be used to help answer such questions. Design: Use of 295 questions asked by Oregon primary care doctors to modify previously developed taxonomy of 1101 clinical questions asked by Iowa family doctors. Setting: Primary care practices in Iowa and Oregon. Participants: Random samples of 103 Iowa family doctors and 49 Oregon primary care doctors. Main outcome measures: Consensus among seven investigators on a meaningful taxonomy of generic questions; interrater reliability among 11 individuals who used the taxonomy to classify a random sample of 100 questions: 50 from Iowa and 50 from Oregon. Results: The revised taxonomy, which comprised 64 generic question types, was used to classify 1396 clinical questions. The three commonest generic types were "What is the drug of choice for condition x?" (150 questions, 11%); "What is the cause of symptom x?" (115 questions, 8%); and "What test is indicated in situation x?" (112 questions, 8%). The mean interrater reliability among 11 coders was moderate (κ=0.53, agreement 55%). Conclusions: Clinical questions in primary care can be categorised into a limited number of generic types. A moderate degree of interrater reliability was achieved with the taxonomy developed in this study. The taxonomy may enhance our understanding of doctors' information needs and improve our ability to meet those needs.